2015
DOI: 10.1026/0049-8637/a000127
|View full text |Cite
|
Sign up to set email alerts
|

What Skills and Abilities Are Essential for Counseling on Learning Difficulties and Learning Strategies?

Abstract: Counseling parents in supporting their children’s learning processes is increasingly emphasized in research on parental involvement and teacher professionalization as a central task of teachers. However, to date there have been few approaches of developing theoretical or psychometric models that describe the internal structure of teachers’ counseling competence in terms of specific skills and abilities as well as of explaining inter-individual differences. The purpose of the current study was to establish a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 20 publications
0
23
0
8
Order By: Relevance
“…It is expected that intervention effects on teachers' counseling competence measured by means of the counseling talk simulations are consistent with measurements determined by means of the scenario test (Bruder, 2011;Gerich et al, 2015).…”
Section: Purpose Of the Current Studymentioning
confidence: 72%
See 4 more Smart Citations
“…It is expected that intervention effects on teachers' counseling competence measured by means of the counseling talk simulations are consistent with measurements determined by means of the scenario test (Bruder, 2011;Gerich et al, 2015).…”
Section: Purpose Of the Current Studymentioning
confidence: 72%
“…In the studies by Bruder (2011) and Gerich et al (2015), the scenario test has been shown to be an objective and economic strategy for the itemized measurement of teachers' counseling competence. Nevertheless, behavior-based instruments for the assessment of teachers' counseling competence, for example, direct performance observation in concrete and realistic application situations (Kane, 1992), have yet to be developed.…”
Section: Behavior-based Instruments For the Assessment Of Teachers' Cmentioning
confidence: 99%
See 3 more Smart Citations